1975
DOI: 10.3109/00016347509157766
|View full text |Cite
|
Sign up to set email alerts
|

Site of Ovulation and Ectopic Pregnancy

Abstract: In a study of 130 tubal pregnancies the relationships as to location of the corpus luteum, the implantation site, and the gross findings of the non-pregnant fallopian tube were analyzed. A contralateral corpus luteum was found in 20% of the cases. Hydrosalpinx, peritubal adhesions and/or thickening of the tubal wall were observed in 33% of the non-pregnant tubes. Grouping by implantation site--ipsilateral or contralateral corpus luteum--showed no statistical differences. The incidence of chronic pelvic inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…This phenomenon of transperitoneal migration of the ovum has been described in the literature in patients having only one tube and one ovary on contralateral sides (9). There are also several case series in the literature describing tubal ectopic pregnancies with contralateral corpora lutea (10)(11)(12)(13). Estimates of the frequency of this occurrence vary considerably, with reports in the literature ranging from 5% to 28% of tubal ectopic pregnancies.…”
Section: Discussionmentioning
confidence: 94%
“…This phenomenon of transperitoneal migration of the ovum has been described in the literature in patients having only one tube and one ovary on contralateral sides (9). There are also several case series in the literature describing tubal ectopic pregnancies with contralateral corpora lutea (10)(11)(12)(13). Estimates of the frequency of this occurrence vary considerably, with reports in the literature ranging from 5% to 28% of tubal ectopic pregnancies.…”
Section: Discussionmentioning
confidence: 94%
“…7,13,15 Furthermore, the supposed association between infertility and transperitoneal migration has led some authors to suggest that oophorectomy, ipsilateral to the salpingectomy, should be performed in certain cases of tubal pregnancy. 13 On the other hand, one case series 14 and one meta-analysis 5 estimated that the incidence of transperitoneal migration is higher than had been suspected. Considering the relatively low incidence of ectopic pregnancy, these studies concluded that the two conditions were unrelated.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] In such cases, fallopian tube obstruction, due to congenital malformations or acquired conditions, has been observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of presentation the average gestation of an unruptured ectopic pregnancy is 6.9 (SD1.9) weeks and 7.2 (SD2.2) weeks if the tube is ruptured. 4 Now a days hormonal imbalance caused by ovulation induction or oestrogen and progesterone administration may affect the transport mechanism of the fallopian tubes. The number, quality & viability of the oocytes may also alter the embryo's Journey to the uterus.…”
Section: Introductionmentioning
confidence: 99%